Arabic Teacher Creativity Towards The Use Of Information Technology In Distance Learning - Nabella Sabella; Hasan Hasan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The main problem in this study, along with the COVID-19 pandemic, which has plagued Indonesia for more than a year, has caused various problems and impacted various aspects of life, especially in education. To reduce the spread of COVID-19, the government enforces distance learning, which also impacts learning Arabic and requires teachers to develop creativity in learning. Using a qualitative field research method, this study aims to determine the creativity of Arabic language teachers in utilizing information technology for distance learning during the covid-19 pandemic. As for some of the media used, such as. Create video content, take advantage of social media, use video conferencing applications such as Zoom and Google Meet, to take advantage of educational website services in the form of Google Classroom and Wordwall games. Based on the results of the analysis conducted by the researchers, this study proved that there are various kinds of teacher creativity in learning Arabic online, such as interactive multimedia, quizzes with google forms, word wall games, and so on. Second, eliminating student learning boredom by developing teacher creativity based on information technology. Third, it is still necessary to conduct information technology-based creativity development training, especially in learning Arabic, because not all Arabic language teachers can develop information technology-based teaching skills. This study proved that there are various kinds of teacher creativity in learning Arabic online, such as interactive multimedia, quizzes with google forms, word wall games. Second, eliminating student learning boredom by developing teacher creativity based on information technology.Keywords: Creativity, Arabic Teacher, Distance Learning, Information Technology.